On the determinacy of complex Jacobi matrices - Beckermann, Bernhard; Smirnova, Mirta Castro (Mathematica Scandinavica, 2004)
The aim of this paper is to explore to which extend the theory of the Hamburger moment problem for real Jacobi matrices generalizes to the case of complex Jacobi matrices. In particular, we characterize the indeterminacy in terms of uniqueness of closed extensions of Jacobi matrices, and discuss the link to the growth of the smallest singular values of the underlying Hankel matrices. As a byproduct, we give a positive answer to the open question whether determinacy is preserved under bounded perturbations.